2016
DOI: 10.1016/j.electacta.2016.06.168
|View full text |Cite
|
Sign up to set email alerts
|

Boron, nitrogen co-doped graphene: a superior electrocatalyst support and enhancing mechanism for methanol electrooxidation

Abstract: :Boron, nitrogen co-doped graphene (BNG) is facilely synthesized by the two-step thermal annealing of graphene in the presence of melamine and boric acid, which is served as a novel support to enhance the catalytic properties of noble metal catalysts for the methanol oxidation reaction (MOR). It is revealed that the BNG support has more defect sites due to the co-doping of boron and nitrogen, so that uniformly dispersed Pt nanoparticles with average size of 2.3 nm are anchored on the surface of BNG support. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…As presented in Figure b, O1s spectrum of Pt/SPG and Pt/3D‐SPG catalysts can be resolved into three forms of oxygen, C=O (530.6 eV), O−C‐O (532.2 eV) and C‐OH (533.5 eV) bonds, respectively . Noteworthy that the intensity of C‐OH bonds in Pt/3D‐SPG are much higher (46.1 %) than those in Pt/SPG (36.6 %), suggesting much more hydroxyls are exposed on the 3D porous network structure surface of Pt/3D‐SPG, consistent with the reported literatures ,. The much more C‐OH bonds contribute to promotion of the oxidation of CO ads on the Pt surface, thereby enhancing the CO‐tolerance of Pt/3D‐SPG catalyst ,…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…As presented in Figure b, O1s spectrum of Pt/SPG and Pt/3D‐SPG catalysts can be resolved into three forms of oxygen, C=O (530.6 eV), O−C‐O (532.2 eV) and C‐OH (533.5 eV) bonds, respectively . Noteworthy that the intensity of C‐OH bonds in Pt/3D‐SPG are much higher (46.1 %) than those in Pt/SPG (36.6 %), suggesting much more hydroxyls are exposed on the 3D porous network structure surface of Pt/3D‐SPG, consistent with the reported literatures ,. The much more C‐OH bonds contribute to promotion of the oxidation of CO ads on the Pt surface, thereby enhancing the CO‐tolerance of Pt/3D‐SPG catalyst ,…”
Section: Resultsmentioning
confidence: 96%
“…It has been confirmed that the single heteroatom (i. e. N, P, B, I and S) doping into graphene framework contribute to charge density redistribution of doped graphene, improving interface interaction between Pt and supports and then leading to significant promotion of MOR performance . Moreover, many researchers have proposed co‐doped graphene with two different heteroatoms to further improve the MOR catalytic activity, due to further increase in content of dopant heteroatoms and triggering synergistic effect between different dopants . Based on our previous researches, S and P co‐doped graphene (SPG) supported Pt nanoparticles (Pt/SPG) catalyst exhibited much better activity and stability than P single doped graphene (PG) supported Pt (Pt/PG) and commercial Pt/C electrocatalyst during the MOR process, owing to production of much more defects sites and significant interaction enhancement between SPG and Pt .…”
Section: Introductionmentioning
confidence: 88%
“…It is known that the decreasing binding energy in XPS spectra is usually caused by the acquiring of extra electrons on corresponding atomic orbitals. For N‐meso‐CNRs, the lone pair of electrons from nitrogen will coordinate to Pd, which increases the electron density of its internal 3d orbital and leads to the decrease of binding energy . For Pd nanoparticles loaded on the supports, N‐meso‐CNRs with higher surface nitrogen contents will coordinate to it at more positions, so that a higher electron density and a lower binding energy can be observed.…”
Section: Resultsmentioning
confidence: 99%
“…This shows the high kinetics for the dehydrogenation of Pt/BNG at low potentials. In addition, the onset potential and peak potential of CO stripping for Pt/BNG are 30 and 20 mV lower than those of Pt/NG, respectively . Besides N doping, the B doping of the graphene leads to the formation of B−C−O bonds, increases the defects of the graphene, including C−OH groups, and enhances the desorption of CO ads species on the Pt active sites by the bifunctional mechanism.…”
Section: Heteroatom‐doped Carbon Supportsmentioning
confidence: 98%
“…The bifunctional mechanism is more pronounced for multiple‐element doping in carbon materials. Du et al . reported that the exchange current density and transfer coefficient for B,N‐codoped graphene supported Pt (Pt/BNG) at low potentials (0.4–0.5 V vs. RHE, 0.5 m H 2 SO 4 ) were 5.7×10 −7 A cm −2 and 0.4, which are 89.5 and 0.3 times higher than those of Pt/NG under the same conditions, respectively.…”
Section: Heteroatom‐doped Carbon Supportsmentioning
confidence: 99%